2015
DOI: 10.1515/chempap-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Liquid–liquid extraction and cloud point extraction for spectrophotometric determination of vanadium using 4-(2-pyridylazo)resorcinol

Abstract: Liquid-liquid extraction (LLE) and cloud point extraction (CPE) of vanadium(V) ternary complexes with 4-(2-pyridylazo)resorcinol (PAR) and 2,3,5-triphenyl-2H-tetrazolum chloride (TTC) were investigated. The optimal conditions for vanadium extraction and spectrophotometric determination were identified. The composition (V : PAR : TTC) of the extracted species was 1 : 2 : 3 (optimal conditions; LLE), 2 : 2 : 2 (low reagents concentrations; LLE), 1 : 1 : 1 (short heating time; CPE), and 1 : 1 : 1 + 1 : 1 : 0 (opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…It forms colored complexes with many metal ions and can be used for their spectrophotometric determination. A well-known disadvantage of this reagent is its insufficient selectivity [1]. Commonly used approaches for increasing the selectivity are masking, precise pH control, introduction of additional reagents for the formation of ternary/multicomponent complexes, derivative spectrophotometry, and application of separation/preconcentration steps, which often demand expensive equipment, high running costs, and well-trained personnel.…”
Section: Introductionmentioning
confidence: 99%
“…It forms colored complexes with many metal ions and can be used for their spectrophotometric determination. A well-known disadvantage of this reagent is its insufficient selectivity [1]. Commonly used approaches for increasing the selectivity are masking, precise pH control, introduction of additional reagents for the formation of ternary/multicomponent complexes, derivative spectrophotometry, and application of separation/preconcentration steps, which often demand expensive equipment, high running costs, and well-trained personnel.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the extracted ternary complex has a composition of 1 : 1 : 2 (Fe-4NC-TTC). One can conclude that the Fe(II)-4NC anionic chelate has a double negative charge, since TTC forms monovalent cation (TT + ) [13,[15][16][17][18][19][20][21][22][23][24][25][26] and the Fe(II)-to-TTC molar ratio is 1 : 2 ( Fig. 5, 2).…”
Section: Doi: 101134/s1070363215080241mentioning
confidence: 99%
“…We previously reported [13] a liquid-liquid extraction-chromogenic system containing Fe(III), 4NC, and a widely used [15][16][17][18][19][20][21][22][23][24][25][26] cationic ion-association reagent, 2,3,5-triphenyl-2H-tetrazolium chloride (TTC). The next step, study of a similar system containing Fe(II) instead of Fe(III), is accomplished here.…”
mentioning
confidence: 99%
“…In general, the most commonly used analyti-cal techniques are flame atomic absorption spectrometry (FAAS), 10,11,12 electrothermal atomic absorption spectrometry (ET-AAS), which is also known as graphite furnace AAS (GF-AAS), 13 inductively coupled plasma mass spectrometry (ICP-MS), 14,15 neutron activation analysis (NAA), 16 inductively coupled plasma-optical emission spectrometry (ICP-OES), 17 fluorometry, 18,19 requiring sample pretreatment steps such as ion-exchange, 20 solid phase extraction (SPE), 21,22 liquid phase microextraction (LPME), 23 and cloud point extraction (CPE). [24][25][26][27][28] CPE is superior to traditional solvent extraction because of its high extraction yield and preconcentration factor, and has several advantages such as simplicity, inexpensiveness, operational safety and use of non-toxic rea gents. 29,30 Before detection, CPE is used as a separation and preconcentration method using a surfactant to cause the generation of micellar surroundings and phase separation when a nonionic surfactant solution (or its mixture with cationic or anionic surfactant) as extractant is heated above the critical temperature.…”
Section: Introductionmentioning
confidence: 99%